Initial mitral comisurotomy in Cuba. Brief historical review - Bárbaro Agustín Armas Pérez; Miguel García Emilio Rodríguez; Leandro Segura Pujals; Miguel García Basulto (ECIMED, 2016)
Introduction: the mitral comisurotomy was the first surgical procedure to solve the stenosis of this valve whose cause cuasi exclusively is the rheumatic fever. The surgical variations in the time have been the digital valvulotomy, the mitral comisurotomy, later surge the plastia with percutaneous balon of election actually, further the valvular substitution.  The purpose is to know and honor the pioneers of the country and province, but before we have to make a synthesis of the appearing of these techniques. Historical course in Cuba: with the poor information was difficult to explain the inicial behavior of this surgery in the country, in this case the capital and to know the pioneers and their rol beginning in the two first decades in 1948 and what happened in the decade of 1950 and the emerging in the following years.  It was nothing easy to investigate at this respect; it is suggest the name of doctors that made first surgery in Cuba and the year, also the first in Camaguey, the date and the constitution of the team that made it.  We have no information about the beginning of the procedures in another province. Conclusion: everything show that the first MC was made in Cuba by Dr. Rodriguez Diaz  in 1950, two years after the first in North America and that in Camaguey the Dr. Respall Hidalgo made the first one in a date so early that it is consider a prowess.      Key words: mitral stenosis, mitral comisurotomy, valvuloplasty, valvulotomy, national precursor